Programa de Artes Escénicas Inclusivas para el Desarrollo de las Inteligencias Múltiples Intrapersonal e Interpersonal, en la Unidad Educativa Santa Rosa de la ciudad de Ambato, 2021-2022 - Freire Pérez, Mercedes Elizabeth (2022)
ABSTRACT: The present research entitled "Inclusive Performing Arts Program for the Development of Multiple Intrapersonal and Interpersonal Intelligences, in the "Santa Rosa" Educational Unit of the city of Ambato, 2021-2022", seeks to design an inclusive performing arts program for the development of interpersonal and intrapersonal intelligences of students. This project was aimed at students in the third year of basic education, and different strategies were investigated to help strengthen self-esteem, self-confidence, empathy and social skills, in order to achieve an integral and full development of individuals. The methodology used was mixed. From the quantitative approach we worked with 70 students, the research technique used was the survey, through which data were collected on performing arts and interpersonal and intrapersonal intelligence; with a qualitative approach, since it is considered as a humanistic study given that the area of knowledge is Educational Sciences. Upon analyzing the results, it was concluded that inclusive performing arts as a didactic tool allows all students to participate in any subject covered in the classroom, because this type of tool is fully adaptable to the educational needs, which is why this program is proposed in which different pedagogical strategies related to performing arts are contemplated, these strategies are focused on developing the interpersonal and intrapersonal intelligence of the students, so it is recommended to apply the detailed strategies in such a way that they contribute to strengthen the aforementioned intelligences, generating inclusion in an effective way. KEYWORDS: Intrapersonal and interpersonal intelligence, program, inclusive performing arts, didactic tool, inclusion, pedagogical strategies.